A mercantilização dos corpos trans em "E se eu fosse pura" de Amara Moira - Silva, Jade Mariam Vaccari Carvalho (2023)
E Se eu fosse pura (2018) is the title of the second edition of the work E Se eu fosse puta by Amara Moira. This research consists of 44 subdivisions in prose and some poems that narrate the story of the author, who became a transvestite activist and doctoral professor in Literature at Unicamp. Thus, this work aimed to investigate the author's work in relation to the theme of the commodification of trans bodies, based on the theoretical assumptions of Foucault (1987), Preciado (2021), among others. For this, we start from an analysis that relates the work to Gender Studies in the area of Literature, citing the author herself who is also a literary critic to analyze her work. In our theoretical foundation, we take into account the almost indebtedness of the research (having in mind that there is only one dissertation in the area of Literary Theory about the analyzed work) we intend to create a reference text when talking about Trans Authorship literature, a theme little discussed in the area of Literature, having in view that Feminist Criticism among other studies have not thought the Trans Authorship in its so specific cut, we use theories of Cultural and Gender Studies as the Queer theory, evidenced by philosopher Judith Butler and transfeminist researchers such as KAAS (2015), Vergueiro (2014), Bagagli (2018), Jesus (2019) among others. The research brings as references researchers of Literary Theory who have developed researches about female authorship, as well as about transvestite characters in literature and the representativeness of Trans Authorship in Brazil: as ALÓS (2021), SILVESTRE (2021), MARTINS (2020), DALCASTAGNÈ (2018), among others.